EVALUASI SISTEM MANAJEMEN K3 DAN MAINTENANCE MENGGUNAKAN METODE FAULT TREE ANALYSIS (FTA) - Darsini, Darsini; Haryono, Sri (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
This study fokuces on three main problems that often occur in V-Bunkers Tanker PTE LTD, namely Main Engine Overhead, Auxiliary Engine Fuel Pump Failuer, and Clogged or dirty Lube Oil Filter. The aim is to provide an occupational safety and health (K3) management system and miimoze the risk of damage to the machine through the application of the Foult Tree Analysis (FA) method. Data were collected through interviews with maintenance operators and direct observation of the ship's operational process. The analysis results showed that Main Engine Overheat was caused by cooling system failure, fuel contamination, and lack of routine maintenance. Auxiliary Engine Fuel Pump Failure occurred due to poor fuel quality, unstable fuel pressure, and component wear. Meanwhile, Clogged or Dirty Lubricating Oil Filters were caused by the use of low-quality lubricants and lack of routine inspections. The impacts of these damages include decreased ship operational efficiency, increased risk of workplace accidents, and impaired crew safety. The application of FTA helps identify the root cause of the damage and provides recommended solutions, such as preventive maintenance, regular replacement of spare parts, and safety training for crew.